STRATEGI PEMBELAJARAN BAGI SISWA INKLUSIF DI KELAS IV SD NEGERI 1 POKA - Usia, Zainal; Elsinora Mahananingtyas; Samuel Patra Ritiauw (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine and describe "learning strategies for inclusive students at SDN 1 Poka". The research method used is a descriptive qualitative research method. The subjects of the study were homeroom teachers and class teachers. The data collection methods used were observation, interviews and documentation. The results of the study showed that: Constraints in inclusive student learning (1) the absence of a special tutor (GPK) (2) teachers do not have experience in inclusive student learning (3) in terms of seating arrangements (4) learning materials are the same as regular student learning materials. The learning planning process of SDN 1 Poka School categorizes inclusive students in class IV (one person) using the same RPP as regular students. In achieving the learning objectives that have been determined, in the implementation of learning, the homeroom teacher and class teacher work together in the learning process, the learning methods used are lecture, question and answer, and discussion methods so that they still involve inclusive students, (slow learners) and learning for inclusive students is quite good because of the motivation given by educators. In the evaluation of learning, there are two assessments at SDN 1 Poka for inclusive students, namely the performance test (oral test) and the written test. The assessment is adjusted to the abilities of inclusive students so that it is different from regular students